The effect of risk management on financial performance of commercial banks in Ethiopia - Abel Worku Tassew; Aregu Asmare Hailu (Financial Studies, 2019)
Efficient and effective performance of banking industry over time is an index of financial stability in any nation. Risk management is a key issue to sustain the financial stability. The presence of different risks in financial industry appeals for effective risk management procedures. As a result, this study examined the effect of risk management on financial performance of 17 Ethiopian Commercial Banks. Quantitative research approach was applied using secondary data for the sample period covered from 2013 to 2017. The collected data was analyzed by using panel random effect regression model. The result of the study shows that credit risk, liquidity risk, operating risk and market risks have significant negative impact on financial performance of commercial banks in Ethiopia. Whereas, bank size as control variable has positive impact on financial performance of commercial banks. The study concludes that credit, liquidity, operation and market risks have significant effects on financial performance of commercial banks in Ethiopia. The study suggests that commercial banks in Ethiopia should manage their loan portfolio and hedge their business risks in the market so as to sustain their financial performance.
Keywords: G32; L25; 330; Effective Risk Management; Financial Stability